Extended Perioperative Antibiotic Coverage in Conjunction with Intraoperative Bile Cultures Decreases Infectious Complications after Pancreaticoduodenectomy. (11th April 2016) - Fathi, Amir H.; Jackson, Terence; Barati, Mehdi; Eghbalieh, Babak; Siegel, Kelly A.; Siegel, Christopher T.
Abstract : Background . Bile contamination from the digestive tract is a well-known risk factor for postoperative complications. Despite the literature concerning prevalence of bacterobilia and fungobilia in patients with biliary pathologies, there are no specific recommendations for perioperative antimicrobial coverage for biliary/pancreatic procedures. We evaluated the effect of at least 72 hours of perioperative broad spectrum antibiotic coverage on outcomes of pancreaticoduodenectomy (PD). Materials and Methods . A retrospective review of all patients at Case Medical Center of Case Western Reserve University undergoing PD procedure, from 2006 to 2011, was performed (n = 122 ). Perioperative data including demographics, comorbidities, biliary instrumentation, antibiotic coverage, culture results, and postoperative outcomes were analyzed. Propensity score matching method was used to match the patients according to duration of antibiotic coverage into two groups: 72 hours (A72) and 24 hours (A24). Results . Longer broad spectrum antibiotic coverage in group A72 resulted in significantly less surgical site infections after PD, compared to routine 24 hours of perioperative antibiotics in group A24. This study did not reveal a statistically significant decrease in postoperative fungal infections in patients receiving preoperative antifungals. Conclusion . Prolonged perioperative antibiotic therapy in conjunction with intraoperative bile cultures decreases the short-term infectious complications of PD, with no significant increase in Clostridium difficile colitis incidence.